TRADISI MASYARAKAT SAMBAS: IDENTIFIKASI NILAI-NILAI KEARIFAN LOKAL DAN EKSISTENSINYA - Januardi, Arif; Superman, Superman; Firmansyah, Haris (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aims to describe in detail the traditions that are still developing and identify the values of local wisdom contained in the traditions of the Sambas community and their existence. the method used in this research is qualitative research, the research location is in Sambas Regency, the research subject is the Sambas community who still carries out the tradition. The tradition of white flour and saprahan is the identity of the Sambas community which has been passed down from generation to generation until now because we can see it because it has a philosophical meaning and is considered to have positive values in society. The values of local wisdom contained in the plain flour and saprahan traditions such as religious values and social values, the existence of the plain flour and saprahan traditions in the Sambas Malay community have become a must to be implemented by every Sambas Malay community. This is because it is considered that the tradition has become a cultural heritage that deserves to be preserved and maintained as well as an inherent pride in the Sambas community.